Understandings of dementia in low and middle income countries and amongst indigenous peoples: a systematic review and qualitative meta-synthesis. (2nd August 2020) - Johnston, Karen; Preston, Robyn; Strivens, Edward; Qaloewai, Sefanaia; Larkins, Sarah
Abstract: Objectives: Dementia is a growing health priority, particularly in less resourced countries and amongst indigenous populations. Understanding cultural meanings ascribed to dementia is an important aspect of policy development and the provision of culturally congruent care and support for people with dementia, their families and the caring professions. This review investigates conceptualizations of dementia amongst indigenous peoples and populations living in low and middle income countries (LMIC), who experience limited diagnosis and formal care for dementia, and how these shape responses to dementia. Methods: A systematic search was conducted for qualitative studies, reported in English, that investigated the perceptions, attitudes or understandings of dementia in LMIC and amongst indigenous populations. A qualitative analysis and meta-synthesis was carried out. Findings: Nineteen articles were included in the review following quality assessment. Dementia was rarely conceptualized as a defined, pathological condition characterized by progressive cognitive decline. Rather, notions of dementia existed within conceptualizations of aging, mental illness, traditional cultural beliefs and the trauma of colonization. Responses to dementia were influenced and perpetuated by community and health providers, and cultural norms for caregiving. Conclusions: There is a need to understand conceptualizations of dementia from the perspective of all stakeholders within a setting, and the dynamic responses that exist between key stakeholders. Community knowledge systems could facilitate understanding about appropriate and acceptable health and community care responses to dementia, and approaches to stigma reduction. Inclusive discussions about dementia are essential if awareness campaigns are to improve the wellbeing of people with dementia and caregivers.